WATER QUALITY MANAGEMENT IN VANNAMEI SHRIMP (Litopenaeus vannamei) CULTURE AT PT. ANUGERAH NUSANTARA KRAKSAAN PROBOLINGGO REGENCY, EAST JAVA PROVINCE - Adriant, Nathania Nurmala Nabilah; Halim, Atika Marisa; Suprakto, Bambang; Ridho, Ridho; Suratman, Suratman (Universitas Mataram, 2025)
Water quality management is the main factor in rearing vannamei shrimp cultivation. Quality shrimp is produced from optimal water quality management. PT. Anugerah Nusantara Kraksaan is a company that operates in the field of rearing vannamei shrimp. So this research aims to determine the application of water quality management in rearing vannamei shrimp (Litopenaeus vannamei) at PT. Anugerah Nusantara Kraksaan, East Java Province. The research was carried out for 1 month from January to February 2025 starting from DOC 68 until DOC 96. This research was carried out on Plots G3, Plots G5, and Plots H4 with concrete construction. The fry used in the research were from PLB (Prima Larvae Bali) on Postlarva 10. Data taken on these water quality parameters were Brightness, Temperature, pH, Dissolved Oxygen, Salinity, Amonnium, Phospat, Alkalinity, and TOM. To overcome fluctuations in environmental parameters, it is necessary to change water, filter, and administer probiotics periodically until the total harvest is achieved. It can be concluded that the results of the best water quality management is in plot G3, because plot G3 can last longer, but plots H4 is the most stable for its water quality even though it ends up being affected by Infectious Myonecrosis disease.